The Impact of Some Internal Factors on the Growth of Unrestricted Investment Accounts in Islamic Banks in Syria (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aims to study the impact of some internal factors on the growth of unrestricted investment accounts in Islamic banks in Syria during the period from 2011 to 2023.The study used the growth of unrestricted investment accounts as the dependent variable, while revenues non-compliant with Islamic Sharia, the rate of return on investment for holders of unrestricted investment accounts, profit equalization reserve, investment risk reserve, operational efficiency, common expenses of the Mudaraba pool, and liquidity were included as independent variables.The study used cross-sectional time series (Balanced Panel data) and applied the ARDL model using the Pooled Mean Group (PMG) estimation method.The study found a significant effect of the internal factors (total revenues and gains non-compliant with Islamic Sharia, the rate of return on investment for holders of unrestricted investment accounts in US dollars, operational efficiency, and common expenses of the Mudaraba pool) on the growth of unrestricted investment accounts in Islamic banks in Syria. The study also found no significant effect of the internal factors (the rate of return on investment for holders of unrestricted investment accounts in Syrian pounds, profit equalization reserve, investment risk reserve and liquidity) in Islamic banks in Syria.The study emphasized the need to consider internal Sharia and financial factors that affect unrestricted investment accounts.
Keywords: Internal Bank Factors, Unrestricted Investment Accounts, Islamic Banks.